Left ventricular deformation associated with cardiomyocyte Ca2+ transients delay in early stage of low-dose of STZ and high-fat diet induced type 2 diabetic rats. Issue 1 (December 2016) - Liu, Xiao-Ying; Liu, Fu-Cheng; Deng, Chun-Yu; Zhang, Meng-Zhen; Yang, Min; Xiao, Ding-Zhang; Lin, Qiu-Xiong; Cai, Shi-Ting; Kuang, Su-Juan; Chen, Jing; Chen, Shao-Xian; Zhu, Jie-Ning; et al.
Abstract Background In the early stage of diabetes, the cardiac ejection fraction is preserved, despite the existence of the subclinical cardiac dysfunction to some extent. However, the detailed phenotype of this dysfunction and the underlying mechanism remain unclear. To improve our understanding of this issue, we used low-dose STZ and high-fat diet to induce type 2 diabetic models in rats. The effects and the mechanism associated with the early stages of the disease were analyzed. Methods The type 2 diabetic mellitus (T2DM) in SD rats were induced through 30 mg/kg STZ and high-fat diet. Two-dimensional spackle-tracking echocardiography (STE) and the dobutamine test were performed to examine the cardiac function. Calcium transients of left ventricular myocytes were detected and the related intracellular signalling factors were analyzed by western blotting. Results After 6-weeks, T2DM rats in left ventricular (LV) diastole showed decreased global and segment strain(S) levels (P < 0.05), both in the radial and circumferential directions. Strain rate (Sr) abatement occurred in three segments in the radial and circumferential directions (P < 0.05), and the radial global Sr also decreased (P < 0.05). In the systolic LV, radial Sr was reduced, except the segment of the anterior septum, and the Sr of the lateral wall and post septum decreased in the circumferential direction (P < 0.05). Conventional M-mode echocardiography failed to detect significant alterations of cardiac performance between the two groups even after 12 weeks, and the decreased ejection fraction (EF%), fractional shortening (FS%) and end-systolic diameters (ESD) could be detected only under stress conditions induced by dobutamine (P < 0.05). In terms of calcium transients in cardiac myocytes, the Tpeak in model rats at 6 weeks was not affected, while the Tdecay1/2 was higher than that of the controls (P < 0.05), and both showed a dose-dependent delay after isoproterenol treatment (P < 0.05). Western blot analysis showed that in 6-week T2DM rats, myocardial p-PLB expression was elevated, whereas p-CaMKII, p-AMPK and Sirt1 were significantly down-regulated (P < 0.05). Conclusion A rat model of T2DM was established by low dose STZ and a high-fat diet. LV deformation was observed in the early stages of T2DM in association with the delay of Ca2+ transients in cardiomyocytes due to the decreased phosphorylation of CaMKII. Myocardial metabolism remodeling might contribute to the early LV function and calcium transportation abnormalities.